Optimization of the fabrication parameters of the Co3O4/SiO2 supported ceramic catalyst for CO gas conversion: Design of experiment for solution combustion synthesis. Issue 9 (1st May 2021) - Yermekova, Zhanna; Roslyakov, Sergey; Trusov, German; Leybo, Denis; Bindiug, Denis; Mukasyan, Alexander
Abstract: We evaluated the temperature of 10% conversion ( T 10 ) of the CO oxidation reaction on the Co3 O4 /SiO2 catalyst as a tool for the rapid optimization of the catalyst synthesis through a simultaneously probabilistic and deterministic approach (SPADA) to the design of experiment (DOE). Multiparameter analysis (5 parameters on 4 levels) with simultaneous modification of several parameters was carried out to improve the solution combustion synthesis of the Co-based catalyst. We studied a four-component chemical system consisting of С2 H5 NO2 (glycine), Co (NO3 )2 ⋅6H2 O (cobalt nitrate), NH4 NO3 (ammonium nitrate), and SiO2 . A mathematical optimization model was built based on 16 experiments. The methodological aspects of the SPADA to the DOE were described and experimentally validated. The response of the T 10 parameter was evaluated as a function of the active mixture composition, calcination parameters, and ratio between active phase and supporting material. Strong and weak parameters were identified, and the optimal synthesis conditions were predicted and experimentally verified.